Cough and Exhaled Nitric Oxide Levels: What Happens with Exercise? - Petsky, Helen; Kynaston, Anne; McElrea, Margaret; Turner, Catherine; Isles, Alan F.; Chang, Anne (Frontiers in Pediatrics, 2013)
Cough associated with exertion is often used as a surrogate marker of asthma. However, to date there are no studies that have objectively measured cough in association with exercise in children. Our primary aim was to examine whether children with a pre-existing cough have an increase in cough frequency during and post-exercise. We hypothesised that children with any coughing illness will have an increase in cough frequency post-exercise regardless of the presence of exercise induced broncho-constriction (EIB) or atopy. In addition, we hypotheised that FeNO levels decreases post-exercise regardless of the presence of EIB or atopy. Children with chronic cough and a control group without cough undertook an exercise challenge, FeNO measurements and a skin prick test and wore a 24-hour voice recorder to objectively measure cough frequency. The association between recorded cough frequency, exercise, atopy and presence of EIB was tested. We also determined if the change in FeNO post exercise related to atopy or EIB. Of the 50 children recruited (35 with cough, 15 control), 7 had EIB. Children with cough had a significant increase in cough counts (median 7.0, IQR 0.5, 24.5) compared to controls (2.0, IQR 0, 5.0, p=0.028) post-exercise. Presence of atopy or EIB did not influence cough frequency. FeNO level was significantly lower post-exercise in both groups but the change was not influenced by atopy or EIB. Cough post-exertion is likely a generic response in children with a current cough. FeNO level decreases post-exercise irrespective of the presence of atopy or EIB. A larger study is necessary confirm or refute our findings.